Web Scraping Untuk Pengambilan Data Transaksi Penjualan Pada Markeplace Toko Online Jogjabatik - Lahmi, Sulahmi; Wardani, Setia; Fairuzabadi, Muhammad (Jurusan Informatika STTR Cepu, 2023)
The online shop Jogjabatik is located at Perum Sidorejo Ngestiharjo, Kasihan, Bantul, which was founded by Mr. Dwi Pudji since 2006 which sells various kinds of batik clothes, traditional clothes, souvenirs and so on. The strategy of having more than one marketplace user makes it overwhelming for employees in the process of managing and preparing sales reports to be reported to the owner. Therefore, the authors designed a system with the help of web scraping techniques on every sale that has the ability to support the formation of an information system capable of absorbing data, presenting data systematically and quickly, so that Jogjabatik online store employees can retrieve detailed data from a web completely. This system is built with PHP programming language with MySQL database. Methods of data collection using the interview method. This Web Scraping system provides information on product sales reports at the Jogjabatik online store by utilizing web scraping techniques which are implemented on 3 marketplace accounts consisting of Lazada, Shopee and Tokopedia to assist Jogjabatik employees in making sales reports.